Jason and Medea’s Relationship in Medea: - Mahbuba Sarker Shama (Crossings, 2017)
Medea in Euripides’ Medea murders her two sons to take revenge on her husband Jason who has married the Corinthian princess Glauce for royal power. However, little attention has been paid towards the cause behind the killing of her sons. This paper will examine the marital relationship between Medea and Jason from the perspective of the colonizer and the colonized and it will show Medea as the victim colonized who kills her brother and leaves her native land Colchis to marry Jason. Jason is presented as the oppressor colonizer who betrays Medea without whom he could have never achieved the Golden Fleece. The terms colonizer and colonized which are at the heart of the postcolonial theory are hardly applied with the play Medea. Therefore, analyzing this topic from the present day postcolonial theory adds a new perspective to this Greek play.